Implementasi Teba Modern Sebagai Solusi Berkelanjutan Pengelolaan Sampah Organik Di Banjar Keliki Kawan, Desa Kelusa - Manik Puryantini (Jurnal Pengabdian Kepada Masyarakat, 2025)
Organic waste management in Kelusa Village, especially in Banjar Keliki Kawan, is a problem for the local community, due to the lack of public awareness of the environment, as well as inadequate facilities. To overcome these problems We carry out community service that focuses on organic waste management through the creation of Modern Teba. This activity aims to increase public awareness of environmental cleanliness and examples of making modern teba in order to reduce the negative impacts of organic waste that is not managed properly. The implementation method includes two main steps. First, socialization to the community to provide an understanding of the concept of Modern Teba, its benefits, and how to process organic waste into compost. Second, making examples of Modern Teba to inspire the community to apply this concept in their respective homes. The results of this community service activity show an increase in public awareness of the importance of organic waste management, increased public concern for environmental cleanliness, and understanding the process of managing and composting with modern Teba independently. Keywords: Waste; Modern Teba; Compost